How can we reduce the risk of mother-to-child transmission of HIV during invasive obstetric procedures? - C N Mnyani; E Nicolaou; E Bera; V Black; J C Hull; J A McIntyre (AOSIS, 2011)
Antenatal invasive obstetric procedures may be diagnostic or therapeutic, and are performed at different stages of pregnancy for various indications. The commonest indication for an invasive procedure during pregnancy is for fetal karyotyping when a chromosomal abnormality or a genetic defect is suspected, either from the couple's history or from ultrasound assessment of the fetus. Other less common but equally important indications may be diagnostic (fetoscopy, fetal tissue sampling, estimation of fetal haemoglobin) or therapeutic (aspiration of various fetal cavities, fetal blood transfusion and embryo reductions). In a high HIV prevalence setting like South Africa, a significant proportion of pregnant women in need of invasive procedures will be HIV-infected.